2016
DOI: 10.1007/s00253-016-7853-5
|View full text |Cite
|
Sign up to set email alerts
|

Current advances in molecular methods for detection of nitrite-dependent anaerobic methane oxidizing bacteria in natural environments

Abstract: . (2016) Current advances in molecular methods for detection of nitrite-dependent anaerobic methane oxidizing bacteria in natural environments. Applied Microbiology and Biotechnology, 100 (23). pp. 9845-9860. Permanent WRAP URL:http://wrap.warwick.ac.uk/86286 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 74 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The catalyzed reporter deposition-FISH method was used to detect NC10 bacteria in the sediments of Lake Biwa, which marks the first application of the FISH method in environmental samples. However, for the purpose of environmental detection, the FISH method is considered less sensitive compared with the PCR approach and could be limited if the abundance of the target microorganism is low in the environment (Chen et al, 2016).…”
Section: Amo Reactions With Different Eacceptorsmentioning
confidence: 99%
“…The catalyzed reporter deposition-FISH method was used to detect NC10 bacteria in the sediments of Lake Biwa, which marks the first application of the FISH method in environmental samples. However, for the purpose of environmental detection, the FISH method is considered less sensitive compared with the PCR approach and could be limited if the abundance of the target microorganism is low in the environment (Chen et al, 2016).…”
Section: Amo Reactions With Different Eacceptorsmentioning
confidence: 99%
“…The metabolism of Ca. M. oxyfera is also complex and unusual, because despite being considered an anaerobic microorganism, it is able to oxidize CH 4 using enzymes found in aerobic methanotrophs (Ettwig et al, 2010) such as the particulate methane-monooxygenase (pMMO), encoded in the pmoA gene, which has been used as a biomarker of N-damo bacteria in marine systems (e.g., Chen et al, 2016;Padilla et al, 2016). Metagenomic evidence suggests that Ca.…”
Section: Nitrate/nitrite-dependent Anaerobic Methane Oxidation (N-damo)mentioning
confidence: 99%
“…DAMO bacteria, belonging to the NC10 phylum ( Ettwig et al, 2010 ), is one of the major functional microorganisms participating in DAMO process. Up to now, five phylogenetically distinct subgroups of DAMO bacteria (Groups A–E) have been verified ( Chen et al, 2016 ), among which Group A and Group B were widely distributed in freshwater ecosystem. For example, Group B was more abundant than Group A in the Qiantang River ( Shen et al, 2014 ), while the dominant subgroups were found to be distinct in different reaches in the Wuxijiang River ( Cheng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%